2020
DOI: 10.3389/fgene.2020.00518
|View full text |Cite
|
Sign up to set email alerts
|

Improving Industrially Relevant Phenotypic Traits by Engineering Chromosome Copy Number in Saccharomyces pastorianus

Abstract: The lager-brewing yeast Saccharomyces pastorianus is a hybrid between S. cerevisiae and S. eubayanus with an exceptional degree of aneuploidy. While chromosome copy number variation (CCNV) is present in many industrial Saccharomyces strains and has been linked to various industrially-relevant traits, its impact on the brewing performance of S. pastorianus remains elusive. Here we attempt to delete single copies of chromosomes which are relevant for the production of off-flavor compound diacetyl by centromere s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…The latter include ploidy changes, aneuploidies/chromosome copy number variations (CCNVs), loss of heterozygosity (LOH), gross chromosomal rearrangements (GCRs), and mitotic crossing overs (Peter et al, 2018; van den Broek et al, 2015; Zhu et al, 2016). These phenomena can alter their industrial performance and may happen very rapidly (Gorter de Vries et al, 2020; Kadowaki et al, 2017; Large et al, 2020; Morard et al, 2019, 2020; Zhang et al, 2016). Along with point mutations, these GSV events result in clonal populations gradually accumulating differences in various traits, leading to clonal heterogeneity, clonal interference (competition among isogenic asexual lineages), and hence the emergence of so‐called subclonal lineages, reminiscent of the experimental evolution setups conducted with laboratory strains (Blundell et al, 2018; Lang et al, 2011; Large et al, 2020; Payen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The latter include ploidy changes, aneuploidies/chromosome copy number variations (CCNVs), loss of heterozygosity (LOH), gross chromosomal rearrangements (GCRs), and mitotic crossing overs (Peter et al, 2018; van den Broek et al, 2015; Zhu et al, 2016). These phenomena can alter their industrial performance and may happen very rapidly (Gorter de Vries et al, 2020; Kadowaki et al, 2017; Large et al, 2020; Morard et al, 2019, 2020; Zhang et al, 2016). Along with point mutations, these GSV events result in clonal populations gradually accumulating differences in various traits, leading to clonal heterogeneity, clonal interference (competition among isogenic asexual lineages), and hence the emergence of so‐called subclonal lineages, reminiscent of the experimental evolution setups conducted with laboratory strains (Blundell et al, 2018; Lang et al, 2011; Large et al, 2020; Payen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in the strains sequenced to the date, aneuploidy is found in industrial strains that are often polyploid [51–53], which is also the case for allopolyploids of the genus, suggesting a link between genome stability, aneuploidy and hybridization in domestication. Furthermore, large difference of aneuploidy in a population has been coupled with phenotypic diversity, ultimately facilitating large phenotypic leaps [54, 55]. In general, it has been revealed that the genome structure is much less stable than what was classically thought, with increasing evidence that it could be an important aspect of evolution and domestication.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genome diversity of lager yeast strains is thought to be limited due to an evolutionary bottleneck that occurred during the industrialization of lager beer production ( Gallone et al 2019 ). However, extra-variation and innovation in the lager beer industry could be achieved by screening for different ploidy levels yeasts in available collections or by artificially increasing the number of chromosome copies by genetic modification, physical or chemical treatments ( Gorter de Vries et al 2017 , 2020 ).…”
Section: Discussionmentioning
confidence: 99%